THE SUBSTANCE AND RELEVANCE OF THE CONCEPT OF MARRIAGE AGE IN CONTEMPORARY ISLAMIC FAMILY LAW: AN ANALYSIS OF THE DISCOURSE ON EARLY MARRIAGE AMONG MUSLIM FIGURES - Adawiyah, Robiatul (Universitas Islam Negeri Mataram, 2025)
This study examines the substance and relevance of the concept of marriage age within various contemporary Islamic family laws, particulary focusing on Indonesia and other muslim-majority countries. The research addresses two main problems. First, it examines the comprehensive provisions on the minimum marriage age as regulated by Indonesian law and by comparative Islamic family laws, taking into account biological, psychological, and social maturity. Second, it analyzes the relevance and alignment between statutory marriage-age regulations and the perspectives of religious figures who advocate early marriage, including their philosophical, social, and religious arguments. Employing a normative juridical approach combined with qualitative content analysis, this study reviews primary legal sources such as Law Number 1 of 1974 and its amendment through Law Number 16 of 2019 in Indonesia, the Compilation of Islamic Law (KHI), as well as scholarly literature on the alignment and conflicts between positive law and Islamic legal principles. The findings reveal that Indonesia's legal provision setting the minimum marriage age at 19 years for both men and women aligns with the maqasid al-syariah principles aimed at protecting life (hifz al-nafs), intellect (hifz al-‘aql), and progeny (hifz al-nasl). Nonetheless, there remains a dichotomy in religious discourse, where some leaders justify early marriage based on traditional interpretations emphasizing baligh (puberty) and social practices. In contrast, others caution against its health and psychosocial risks, advocating adherence to statutory age limits. The study concludes by recommending a multidisciplinary, participatory approach involving government, religious leaders, local customs authorities, and civil society to enhance education, socialization, and legal enforcement, thereby effectively addressing the challenges posed by early marriage practices. This balanced framework harmonizes religious values, human rights, and legal norms toward creating healthy, prosperous, and stable families.